PENILAIAN HIASAN SULAM SASHIKO PADA BUSANA ANAK - Zahra Al Syifa, Siti; Radiona SP, Vivi (Practice of Fashion and Textile Education Journal, 2021)
This study aims to obtain and analyze the assessment of sashiko embroidery on children's clothing which is assessed based on the requirements for making a good decoration design, aspects of design elements and design principles. This study uses a pre-experimental method and a form of One-Shoot Case Study design. The data collection technique in this study was carried out using a questionnaire to five expert panelists as research subjects. The results showed that overall, the assessment of sashiko embroidery on children's clothing was in the very good category based on the requirements for making a good decoration design including limited use of decorations, suitability of decoration, sufficient space, and suitability of decoration materials. Assessment based on aspects of design elements which include shape, size, texture, and color are in the very good category. Assessment based on aspects of design principles which include harmony, rhythm, proportion, balance and center of attention are also in the very good category. Model 5 was excellent with the highest score covering all aspects, so it can be concluded that sashiko embroidery can be used as an alternative decoration on children's clothing